Exploring the Impact of Obesity on Skeletal Muscle Function in Older Age - Morgan, Paul T.; Smeuninx, Benoit; Breen, Leigh (Frontiers in Nutrition, 2020)
Sarcopenia is of important clinical relevance for loss of independence in older adults. The prevalence of obesity in combination with sarcopenia (‘sarcopenic-obesity’) is increasing at a rapid rate. However, whilst the development of sarcopenia is understood to be multi-factorial and harmful to health, the role of obesity from a protective and damaging perspective on skeletal muscle in ageing, is poorly understood. Specifically, the presence of obesity in older age may be accompanied by a greater volume of skeletal muscle mass in weight-bearing muscles compared with lean older individuals, despite impaired physical function and resistance to anabolic stimuli. Collectively, these findings support a potential paradox in which obesity may protect skeletal muscle mass in older age. One explanation for these paradoxical findings may be that the anabolic response to weight-bearing activity could be greater in obese vs. lean older individuals due to a larger mechanical stimulus, compensating for the heightened muscle anabolic resistance. However, it is likely that there is a complex interplay between muscle, adipose, and external influences in the ageing process that are ultimately harmful to health in the long-term. This narrative briefly explores some of the potential mechanisms regulating changes in skeletal muscle mass and function in ageing combined with obesity and the interplay with sarcopenia, with a particular focus on muscle morphology and the regulation of muscle proteostasis. In addition, whilst highly complex, we attempt to provide an updated summary for the role of obesity from a protective and damaging perspective on muscle mass and function in older age. We conclude with a brief discussion on treatment of sarcopenia and obesity and a summary of future directions for this research field.